Modelling and analysing deadlock in flexible manufacturing system using timed petri net - Taha, Assem Hatem; Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas (Deerhill Publishing, 2017)
Flexible manufacturing system (FMS) has several advantages compared to conventional systems such as higher machine utilization, higher efficiency, less inventory, and less production time. On the other hand, FMS is expensive and complicated. One of the main problems that may happen is the deadlock. Deadlock is a case that happens when one operation or more are unable to complete their tasks because of waiting of resources that are used by other processes. This may occur due to inappropriate sharing of the resources or improper resource allocation logic which may lead to deadlock occurrence due to the complexity of assigning shared resources to different tasks in an efficient way. One of the most effective tools to model and detect the deadlocks is the petri net. In this research the MATLAB software was used to detect the deadlock in two parallel lines with one shared machines. The analysis showed that the highest utilization is in transition t4 with 71% and the longest waiting time is in place p4 at 72 seconds. Hence,deadlock was located there as parts wait to be processed by machine 1 which is busy to perform processes on parts in both lines.